A novel coupling reaction of α-halo ketones promoted by SmI3/CuI. Issue 31 (10th March 2016) - Liu, Yongjun; Zhao, Hengmin; Tian, Guang; Du, Feng; Qi, Yan; Wen, Yonghong
Abstract : In the presence of SmI3 and catalyzed by CuI in DMF, α-haloketones were transformed unexpectedly into α-hydroxy-1, 4-diketones. The mechanism was probed and DMF was assumed to play a dual role both as a hydroxyl source and as a solvent. Abstract : With SmI3 as the Lewis acid and catalyzed by CuI in DMF, α-haloketones were transformed unexpectedly into α-hydroxy-1, 4-diketones in good to moderate yields. The mechanism was probed and a plausible reaction pathway was proposed. DMF was assumed to play a dual role both as a hydroxyl source and as a solvent.